Adolescents' Perspectives on Coping with Bullying in the Digital Environment - Bilha Paryente (MDPI AG, 2024)
This study examined the coping process of adolescents in the construction of a sense of coherence after experiencing bullying events in the digital environment. The content analysis of semi-structured interviews with 20 adolescents aged 14 to 18 (M = 16.85) revealed three themes: (1) the comprehension of the bullying as stemming from hatred and boredom; (2) managing the bullying by turning to the bully asking that they stop, deleting and forgiving after the event, and coping through self-isolation and with the support of family and friends; and (3) the emotional processing of anger, embarrassment, and sadness. All the data correlated with the a priori themes of the salutogenic approach, demonstrating a significant expression of the components of a sense of coherence. Understanding the adolescents' coping process and their construction of a sense of coherence following their experience of cyberbullying may help practitioners design and implement tailored interventions for adolescents and their educators who are increasingly confronted with this issue.